Academic career in accounting: evidence from the perspective of professors of stricto-sensu courses - Kruger, Silvana Dalmutt; Santos, Edicreia Andrade; Hillen, Cristina (Advances in Scientific and Applied Accounting, 2024)
Objective: This study sought to understand how gender biases are perceived by teachers and their impact on academic careers in Postgraduate Programs (PPG) in accounting. Methodology: Semi-structured interviews were conducted with nine professors from different PPGs, and the data were analyzed using discursive textual analysis. Results: The interviews revealed gender biases that influence academic performance, sometimes in subtle ways. Biases were observed in relation to female professors, who were often underestimated by male colleagues, even when they were more productive or made greater contributions to the program. In addition, discrimination related to motherhood was reported, whether for being mothers or expressing the desire to become one. Once identified, these biases impacted the professors' careers, becoming explicit in their narratives. However, there was no convergence in perceptions: five respondents clearly recognized the presence of gender biases, while four did not identify them as evident. Contributions: It is assumed that the environment and culture of PPGs, as well as the professors' life histories, educational trajectories, and length of professional experience, influence their perceptions of gender biases. The results suggest the need for systemic changes to promote gender equality, including the adoption of institutional policies that provide support to women in academia and encourage female representation in leadership positions. The research also highlights the importance of further studies on the impact of motherhood and family responsibilities on women’s career progression.